Adult learning : linking theory and practice - Merriam, Sharan B. (Jossey-Bass, 2014)
"Solidly grounded in theory and research, but concise and practice-oriented, Adult Learning: Linking Theory and Practice is perfect for graduate students and practitioners alike. The expert authors have infused each chapter with teaching and instructional applications as well as personal relevance for the reader. The contents covers: Adult Learning in Today's World--globalization; technology; social networking; formal, non-formal, and informal learning The Culture and Context in Adult Learning The Foundations of Learning Theory--behaviorism, cognitive psychology, social constructivism, situated cognition Andragogy Self-directed Learning Transformative Learning The Body and Spirit in Learning Experience and Learning Motivation and Learning The Brain and Mind, including neuroscience Intelligence--practical and emotional intelligence, learning and cognitive styles Critical Thinking and Critical Perspectives "--